Pengaruh Literasi Keuangan terhadap Inklusi Keuangan melalui Financial Technology pada UMKM di Bandar Lampung - I Nyoman Patra Kusuma (Universitas Tarumanagara, 2020)
This study aims to determine the effect of financial literacy on financial inclusion, financial literacy on financial technology and financial technology on financial inclusion at UMKM in Bandar Lampung. The number of samples used was one hundred respondents using a purposive sampling method. The results of the analysis use Smart PLS v.03 to produce significance values for financial literacy variables for financial inclusion, financial literacy for financial technology and financial technology for financial inclusion at UMKM in Bandar Lampung smaller than the level of significance (α = 0.05). So it can be seen that the financial literacy variable partially has a significant effect on financial inclusion and financial technology. While the financial technology variable has no significant effect on UMKM financial inclusion in Bandar Lampung.